El sentido de vida del interno de medicina en la práctica hospitalaria, basado en la relación médico paciente. celaya guanajuato, méxico - García Valenzuela, Patricia Alejandra (2013)
The objective of the study was the design of an instrument quantitative; to measure the sense of life in hospital practice, taking as doctor-patient relationship based on internal students of undergraduate in two hospitals headquarters of Celaya Gto. Mexico. Labor sought to answer the following question: does relationship exists between clearly explain the meaning of life in hospital clinical practice, with the variables of respect, empathy, warmth, attitude, and reason, the inmates of medicine? It is a descriptive, transversal, and applied research. The universe of study was of medicine internal undergraduate students of both sexes who were two hospitals headquarters of the Health Sector of the State of Guanajuato, in the period from January to June 2012. The instrument consists of 50 reagents with Likert scale with 4 response options. Comprises six variables: warmth in the treatment, listen carefully to the patient, explain with clarity and plain language everything concerning his illness, be empathetic, attitude to establish an adequate and cordial medical patient and relationship with team health, respect, reason. The results show a global reliability of 0.829 measured with Cronbach's Alpha, with an homogeneous behavior in them, that will be useful for feedback academic programs and paths of formation, looking for the achievement of the profile of graduation, closely linked with the characteristics of the sense of life that they concern some authors at all times.